Hubungan Dukungan Suami terhadap Pelaksanaan Inisiasi Menyusu Dini (IMD) di Rumah Sakit - Rais Sholeh; Agrina Agrina; Safri Safri (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2019)
Early breastfeeding initiation was the began of early breastfeeding with the mother at least one hour after birth. This research aims to determine correlation between husband's support for the implementation of early breastfeeding. The research method used is quantitative by using a research design that is descriptive correlation with cross sectional approach. Sampling method using accidental sampling technique with total sample 30 respondents. This research used questionnaires and observation sheet as measuring instrument. The inclusion criteria in this studied were normal birth mothers without any indication and complications such as Pre Eclampsia Severe and Hemoraghic Post Partum, normal-born infants who did not experience Low Birth Weight and Asphyxia, and mothers was accompanied by the husband during labor.Research results will of analyzed using alternative test Fisher Exact. The results showed significant correlatied between husband’s supported for implementation of early breastfeeding (p value 0,030). Healthcare workers can be still develop related to IMD in post partum with the of husband's supported so that implementation of IMD for children can be perfect.